Design and application of a point-of-care testing system for triple detection of SARS-CoV-2, influenza A, and influenza B - Yang, Huan; Zhang, Xiaoming; Li, Yating; Deng, Jing; Liu, Zhongming; Chen, Qiyue; Zhang, Haiyan (Frontiers in Bioengineering and Biotechnology, 2024)
To mitigate the continued impact of SARS-CoV-2, influenza A, and influenza B viruses on human health, a smartphone-based point-of-care testing (POCT) system was designed to detect respiratory pathogens through a nucleic acid test. This compact, light-weight, highly automated, and universal system enables the differential diagnosis of SARS-CoV-2, influenza A, and influenza B in approximately 30 min in a single-tube reaction. Numerous hospitals and disease control and prevention center assessed the triple POCT system's detection threshold, sensitivity, specificity, and stability, and have concluded that all the assessments were comparable to those of fluorescent quantitative polymerase chain reaction (PCR)-based testing. The triple POCT system is suitable as an onsite rapid-diagnosis device, as well as for pathogen screening at airports and customs.